KONSUMSI PANGAN PADA BALITA STUNTING : A CASE STUDY - Aries Chandra Anandhita; Gita Marini; Rahma Nadine Az Zahra (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Stunting is a condition where the height or body length of children under five does not match their age as evidenced by the length or height exceeding the standard deviation of the child's growth. The purpose of this study was to identify the food consumption of stunting toddlers in the Ngagelrejo Community Health Center Work Area. The research design used is descriptive with a case study approach. This data collection uses the 3x24 hour food recall method by recording everything consumed by toddlers during the last 24 hours. The prevalence of stunting in Indonesia is 24.4%. In East Java the incidence of stunting in 2021 is 23.5%, while the incidence of stunting inSurabaya according to the BKKBN (2022) is 20%. The results showed that two out of five toddlers only consumed rice and side dishes or rice and vegetable soup only. Two out of five toddlers rarely eat fruit. Four out of five toddlers have a frequency of consuming snacks more than the main food. Three out of five toddlers experience alack of energy. The energy coverage for the three toddlers was 1577 kcal for the first respondent, 1010.2 kcal for the second respondent and 643.2 kcal for the fifth respondent. Five toddlers are deficient in Vitamin D and Calcium. The coverage of vitamin D in the first respondent was 5.6 mcg, in the second respondent 3 mcg, in the third respondent 0.8 mcg, in the fourth respondent 4.1 mcg, and in the fifth respondent 0 mcg. The coverage of calcium consumption in the first respondent was 539.7 mg, the second respondent was 236.8 mg, the third respondent was 496.1 mg, the fourth respondent was 325.3 mg, and the fifth respondent was 267.5 mg.